Influencing Factors of Competency Achievement in Fiber Optic Installation Engineering: A Study on Vocational School Graduates in Indonesia - Pujianto, Pangadongan Elfin; Kustono, Djoko; Elmunsyah, Hakkun (Pascasarjana Universitas Negeri Malang (UM), 2024)
This study investigates the factors influencing the achievement of competencies in the field of Fiber Optic Installation Engineering (TIFO) among vocational school graduates in Indonesia and their subsequent performance in the workforce. Utilizing a quantitative approach, the research examines the relationship between several key variables, including national examination scores, quality of infrastructure, teaching competence, and telecommunication systems subject scores. Path analysis structural equation modeling was employed to determine the direct and indirect effects of these variables on TIFO competency achievement and graduates’ performance. The findings reveal that the quality of infrastructure is the most significant contributor to competency achievement, accounting for 36.24% of the variance. Teaching competence also plays a crucial role, contributing 12.82% to the attainment of competencies. Moreover, the study demonstrates that the achievement of TIFO competencies significantly impacts the performance of vocational school graduates in the industrial sector, explaining 71.9% of their overall performance. These results underscore the importance of high-quality infrastructure and effective teaching in vocational education, highlighting their roles in enhancing competency development and employability among graduates. The study concludes that focused improvements in these areas could substantially benefit the vocational education system, aligning educational outcomes more closely with industry needs and enhancing the employability and performance of graduates in the workforce.DOI: 10.17977/jps.v12i32024p111